2015
DOI: 10.1177/1467358415580360
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, efficacy beliefs, and willingness to pay for environmental protection when travelling

Abstract: Environmental sustainability may be seen as a collective challenge that can only be met if a sufficient number of individuals cooperate. Whether or not individual tourists are willing to contribute their share may thus depend not only on the degree to which they think that environmental sustainability is important (attitudes), but also on the degree to which they think that other tourists hold similar attitudes (social comparison). Other possible influences are beliefs that one's own behaviour can make a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 46 publications
6
59
2
Order By: Relevance
“…Research suggests that strengthening these beliefs might promote sustainable consumption decisions at home (Gupta & Ogden, 2009;Hanss & Böhm, 2010;Hanss, Böhm, Doran, & Homburg, 2016) and on vacation (Doran et al, 2015). In their study, Doran et al (2015) found that people with a strong sense of self-efficacy (e.g. being confident that their choices of environmentally friendly transportation can help reduce carbon emissions) were also more likely to be willing to pay for environmental protection as tourists.…”
Section: Efficacy Beliefsmentioning
confidence: 98%
See 4 more Smart Citations
“…Research suggests that strengthening these beliefs might promote sustainable consumption decisions at home (Gupta & Ogden, 2009;Hanss & Böhm, 2010;Hanss, Böhm, Doran, & Homburg, 2016) and on vacation (Doran et al, 2015). In their study, Doran et al (2015) found that people with a strong sense of self-efficacy (e.g. being confident that their choices of environmentally friendly transportation can help reduce carbon emissions) were also more likely to be willing to pay for environmental protection as tourists.…”
Section: Efficacy Beliefsmentioning
confidence: 98%
“…In a social dilemma context, the term self-efficacy is used somewhat differently, referring to judgments about whether one's contribution helps the group to secure some valued collective outcome (Kerr, 1992). Research suggests that strengthening these beliefs might promote sustainable consumption decisions at home (Gupta & Ogden, 2009;Hanss & Böhm, 2010;Hanss, Böhm, Doran, & Homburg, 2016) and on vacation (Doran et al, 2015). In their study, Doran et al (2015) found that people with a strong sense of self-efficacy (e.g.…”
Section: Efficacy Beliefsmentioning
confidence: 99%
See 3 more Smart Citations